Induction of interferon‐λ contributes to Toll‐like receptor‐3‐activated hepatic stellate cell–mediated hepatitis C virus inhibition in hepatocytes. Issue 6 (7th January 2013) - Wang, Y.; Li, J.; Wang, X.; Ye, L.; Zhou, Y.; Ho, W.
Summary There is limited information about the role of hepatic stellate cells (HSC) in liver innate immunity against hepatitis C virus (HCV). We thus examined whether HSC can produce antiviral factors that inhibit HCV replication in human hepatocytes. HSC expressed functional Toll‐like receptor 3 (TLR‐3), which could be activated by its ligand, polyinosine‐polycytidylic acid (poly I:C), leading to the induction of interferon‐λ (IFN‐λ) at both mRNA and protein levels. TLR‐3 signalling of HSC also induced the expression of IFN regulatory factor 7 (IRF‐7), a key regulator of IFN signalling pathway. When HCV JFH‐1‐infected Huh7 cells were co‐cultured with HSC activated with poly I:C or incubated in media conditioned with supernatant (SN) from poly I:C‐activated HSC, HCV replication was significantly suppressed. This HSC SN action on HCV inhibition was mediated through IFN‐λ, which was evidenced by the observation that antibody to IFN‐λ receptors could neutralize the HSC‐mediated anti‐HCV effect. The role of IFN‐λ in HSC‐mediated anti‐HCV activity is further supported by the observation that HSC SN treatment induced the expression of IRF‐7 and IFN‐stimulated genes (ISGs), OAS‐1 and MxA in HCV‐infected Huh7 cells. These observations indicate that HSC may be a key regulatory bystander, participating in liver innate immunity against HCV infection using an IFN‐λ‐dependent mechanism.